2015
DOI: 10.1177/1933719114542015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Pakistani Women With Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the major cause of anovulatory infertility. Although the genetic basis of PCOS is not well understood, it is a common metabolic and endocrine disorder. This study investigates the possible genomic variants associated with PCOS in Pakistani women from the Punjab region. DNA samples from 96 patients with genetically unrelated PCOS and 96 controls were analyzed by direct sequencing to determine the polymorphisms of different loci on follicle-stimulating hormone receptor (fshr),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Conversely, the GA genotype of rs1999805 in ESR1 , and the TT genotype of rs1801133 in MTHFR were significantly associated with increased risk of PCOS. Associations of ESR1 rs9340799 (25), HMGA2 rs2272046 (21), and MTHFR rs1801133 (32) with PCOS risk have been reported in other studies. In contrast, our results appear to provide the first evidence linking rs1999805 in ESR1 and rs709154 in PPARG with PCOS risk in a Chinese population.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Conversely, the GA genotype of rs1999805 in ESR1 , and the TT genotype of rs1801133 in MTHFR were significantly associated with increased risk of PCOS. Associations of ESR1 rs9340799 (25), HMGA2 rs2272046 (21), and MTHFR rs1801133 (32) with PCOS risk have been reported in other studies. In contrast, our results appear to provide the first evidence linking rs1999805 in ESR1 and rs709154 in PPARG with PCOS risk in a Chinese population.…”
Section: Discussionsupporting
confidence: 58%
“…Whatever the underlying mechanism, the association between ESR1 polymorphism and risk of PCOS appears to depend in complex ways on ethnicity. A Pakistani study linked the CC genotype of ESR1 rs2234693, the GG genotype of rs9340799, and the CT genotype of rs8179176 with elevated disease risk (25). However, studies in Greeks (34) and Caucasians (35) revealed no differences in frequencies of these genotypes between PCOS patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies related to LHβ gene polymorphisms have focused mainly on human reproductive disorders [24,25]. Basavarajappa et al identified seven different variants of the LHβ gene in the Indian river buffalo (Bubalus bubalis) based on a polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) analysis [26].…”
Section: Discussionmentioning
confidence: 99%
“…The study on genes susceptible to PCOS has focused mainly on gene polymorphisms that encode sex hormones and regulatory proteins such as folliclestimulating hormone ß, follicle-stimulating hormone receptor, luteinizing hormone/choriogonadotropin receptor (LHCGR), estrogen receptor alphareceptor (ESR1), and estrogen receptor ß (ESR2). Variants of genetic markers have implications for the predisposition of PCOS; however, there are no variants that are directly and repeatedly linked to PCOS [3], [6].…”
Section: Introductionmentioning
confidence: 99%